Characterization of the methanotrophic bacterial community present in a trichloroethylene-contaminated subsurface groundwater site. - Bowman, J P (1993)
Groundwater, contaminated with trichloroethylene (TCE) and tetrachloroethylene (PCE), was collected from 13 monitoring wells at Area M on the U.S. Department of Energy Savannah River Site near Aiken, S.C. Filtered groundwater samples were enriched with methane, leading to the isolation of 25 methanotrophic isolates. The phospholipid fatty acid profiles of all the isolates were dominated by 18:1 omega 8c (60 to 80%), a signature lipid for group II methanotrophs. Subsequent phenotypic testing showed that most of the strains were members of the genus Methylosinus and one isolate was a member of the genus Methylocystis. Most of the methanotroph isolates exhibited soluble methane monooxygenase (sMMO) activity. This was presumptively indicated by the naphthalene oxidation assay and confirmed by hybridization with a gene probe encoding the mmoB gene and by cell extract assays. TCE was degraded at various rates by most of the sMMO-producing isolates, whereas PCE was not degraded. Savannah River Area M and other groundwaters, pristine and polluted, were found to support sMMO activity when supplemented with nutrients and then inoculated with Methylosinus trichosporium OB3b. The maximal sMMO-specific activity obtained in the various groundwaters ranged from 41 to 67% compared with maximal rates obtained in copper-free nitrate mineral salts media. This study partially supports the hypothesis that stimulation of indigenous methanotrophic communities can be efficacious for removal of chlorinated aliphatic hydrocarbons from subsurface sites and that the removal can be mediated by sMMO.